Rupturing fungal cell walls for higher yield of polysaccharides: Acid treatment of the basidiomycete prior to extraction - Trygg J.; Beltrame G.; Yang B. (ELSEVIER SCI LTD, 2025)
The fungal cell wall of Agaricus bisporus powder was degraded by ethanol-acid treatment in order to improve the yield of the hot water extractions. Polysaccharides from multiple hot water extractions of treated and untreated mushroom were precipitated with ethanol and characterised separately. The treatment and the sequenced extractions changed the anomeric compositions, the molecular weights, and the sugar contents of the extracted polysaccharides. The total yield of the first extraction of treated A. bisporus increased by 46% with over 10 percentage points higher glucan content compared to untreated batch. Bioactivities were decreasing within the extraction batches and after the treatment. This was found to be connected to the amount of polysaccharides and the content of mannitol in the precipitates.